Modified Humic Substances as Soil Conditioners: Laboratory and Field Trials - Natalia A. Kulikova; Alexander B. Volikov; Olga I. Filippova; Vladimir A. Kholodov; Nadezhda V. Yaroslavtseva; Yulian R. Farkhodov; Anna V. Yudina; Vitaly A. Roznyatovsky; Yuri K. Grishin; Oral T. Zhilkibayev; Irina V. Perminova (Agronomy, 2021)
The paper is devoted to the development and performance testing of a soil conditioner based on leonardite humic substances (LHS) modified with 3-aminopropyltriethoxysilane (APTES). The modified HS were obtained by adding APTES to LHS solution at different mass ratios of LHS and APTES, followed by the investigation of siloxane structures using 31Si NMR spectroscopy. The Urbic Technosol was used as a model soil. The size and amount of water-stable soil aggregates were estimated using wet sieving and laser diffraction, respectively. Toxicity was evaluated by monitoring microbial substrate-induced respiration (SIR) and seedling bioassay. Laboratory column experiments demonstrated an increase in water-stability of the 3–5 mm soil aggregates after LHS-APTES application. Field tests showed an increase in the average weighted diameter of micro aggregates (from 59 to 73 μm) and water-stable macroaggregates (from 1.6 to 2.9 mm) due to the LHS-APTES amendment. A substantial increase in SIR from 5 to 9 mg CO2 (kg h)−1 was detected. Better survival of seedlings was observed. The obtained beneficial results indicate that APTES-modified HS can be successfully used as a soil conditioner. The formation of extended siloxane networks was suggested as the main mechanism of the observed improvement in the structure of the amended soils.